"We're not gonna be friends anymore": Associations between viewing relational aggression on television and relational aggression in text messaging during adolescence. Issue 3 (2nd February 2019) - Coyne, Sarah M.; Ehrenreich, Samuel E.; Holmgren, Hailey G.; Underwood, Marion K.
Abstract: A number of studies suggest that adolescents who view relational aggression on television are more likely to engage in higher levels of subsequent relational aggression in social interactions. This study examined longitudinal associations between viewing relational aggression on television and relationally aggressive behavior in text messaging over a 1‐year period during adolescence. Participants were 197 adolescents who completed a number of questionnaires regarding media use and aggression. Adolescents were each given a BlackBerry device and a sample of text messages was coded for aggressive behavior. Results revealed that exposure to relational aggression on television was associated with higher levels of relational aggression in texting one year later, but only for girls. Results are discussed with reference to the General Aggression Model.